Changes in properties of metal-containing raw materials as a result of electric processing - Sakipova, S.E.; Nussupbekov, B.R.; Aitpaeva, Z.K.; Khassennov, A.; Ospanova, D.A.; Stoev, Mitko (Publishing House of the KarSU named after E.A.Buketov, 2013)
The article discusses the results of use of electric pulse technology for processing metal-containing raw materials. It shows the results of the analysis of the elemental composition of ore samples from Nurkazgan and Annensk deposits in Kazakhstan before and after electric pulse processing. The authors obtained data on changes in properties of the samples and on increase in weight concentration of some elements, including rare metals after the electric pulse processing. Application of electric pulse processing of metal-containing and technogenic raw materials makes it possible to obtain dispersion materials with preset parameters and it facilitates efficient extraction of valuable components. It was established that the electric pulse processing technology may be used in practice in enrichment process of metal-containing raw materials.
Keywords: metal-containing and technogenic raw materials; electric pulse processing; materials with preset parameters; enrichment process